Assessing the Effectiveness of Legal Protection for Local Communities in Agrarian Disputes Against Corporations in West Bangka Regency - Gustami, Gustami; Agustina, Enny (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the effectiveness of legal protection for local communities in agrarian disputes with corporations in West Bangka Regency, as well as to identify both legal and non-legal barriers faced by these communities in securing their land rights. The research is based on the Landbow land dispute case in Kelapa Subdistrict, West Bangka, which was won by the local community through a decision by the Administrative Court (PTUN) of Pangkalpinang, Case Number 16/G/PTUN.PGP/2025. The research adopts normative and empirical juridical methods, utilizing statute and case approaches along with interviews with relevant stakeholders. The findings reveal that while normative legal protection exists through national legal instruments, its effectiveness at the implementation level remains weak. Communities frequently encounter obstacles such as delayed responses from local authorities, lack of legal literacy, and corporate dominance. The study recommends strengthening access to legal aid, improving community advocacy capacity, and enhancing local government commitment to agrarian justice.